THE OPERATING COSTS REDUCTION IN CASE OF THE WARNINGS ABOLISHMENT OF THE TRAINS SPEED LIMIT - Chernyshova, O. S. (Science and Transport Progress, 2008)
The results of research of efficiency of elimination of train speed limitations are presented.